Pick your poison - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2018)
Thirteen-year-old code breaker and undercover agent Ruby Redfort can deal with poisonous snake bites and knows how to set up someone to take the fall, but when it come to staying ahead of rumors in Twinford, Ruby doesn't know if she can keep up.